THE USE OF PROBLEM-BASED LEARNING METHODS TO IMPROVE STUDENT’S CRITICAL THINKING SKILLS - Nur Mashani Mustafidah; Ari Susandi; Nurul Huda; Nur Hayati; Arif Susanto (Conciencia, 2022)
This research is a class action research; the subject is the students of class XI IPS 1 MAN 1 Bojonegoro, which amounted to 35 students. This research was conducted four times a meeting and as many as two cycles, each cycle one face-to-face meeting. The data collection methods used were tests, observation, and documentation. The test is used to measure students' critical thinking skills using tests. To process quantitative data using scoring techniques from students' individual scores, the average score of research subjects, and the percentage of classical completeness. The results showed that applying the Problem-Based Learning method made many contributions, including the ease of students in understanding dress code material because of its fun and relaxed delivery. Most students have been able to understand the adab of dressing, but some obstacles lie in student boredom related to learning methods so far; it turns out that during the learning process in class XI US1, the teacher still uses conventional methods, in the form of lectures and assignments so that it has an impact on the condition of students who become passive and bored because learning seems monotonous.